Integral representation of an analytic function in a ring and its applications - Kerekesha, P. V.; Cherskii, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
An integral representation of an analytic function in a ring with corresponding limit values on the boundary is obtained. A new singular integral equation is suggested and solved in quadratures by using an integral representation and by complete investigation of the Cárleman problem for a ring (in the normal case).